A Framework for Abu Dhabi Police Traffic Monitoring and Response System - Abdelfatah, Akmal (2013)
Abstract—The city of Abu Dhabi has witnessed a major growth in its population over the past two decades. This growth has resulted in a significant increase in the number of vehicles in the city. Abu Dhabi Police Department (ADPD) is currently working on the development of a traffic monitoring and response center. The main objective of this paper is to present the main framework for ADPD’s traffic monitoring and response center, which will allow for a more robust operation of the police department activities. The core element of the response system is a microsimulation model for the city. This paper presents the main framework for ADPD traffic center and the initial results of the microsimulation model development. The well-known microsimulation model VISSIM is utilized to create the core of the traffic monitoring and response center, which will allow ADPD to test and investigate different scenarios.